Prevalence of Chronic Kidney Disease in a Nigerian Family Practice Population - Muhammed O. Afolabi; Akintunde E. Abioye-Kuteyi; Fatiu A. Arogundade; Ibrahim S. Bello (South African Family Practice)
Background: Chronic kidney disease (CKD) is a global public health problem, with a greater burden and prohibitive cost of care particularly in developing countries. This study determined the prevalence of chronic kidney disease and identified its associated risk factors in patients attending the Family Practice Clinic, Wesley Guild Hospital, Ilesa, Nigeria.